Le contrat électronique International - Edderouassi, Meryem (Université Grenoble Alpes, 2017)
La réflexion sur la réglementation des contrats électroniques internationaux a pris, ces dernières années, une ampleur sans précédent.L’usage accru des communications électroniques à l’échelle internationale participe de manière remarquable à améliorer l’efficacité des activités économiques et sociales, à renforcer les relations entre Etats et à offrir de nouvelles possibilités de débouchés à des parties et à des marchés auparavant isolés.Pour cette raison, l’adoption de règles uniformes propres à éliminer les obstacles et valoriser les contrats électroniques internationaux serait susceptible de renforcer la certitude juridique et la prévisibilité commerciale des contrats internationaux et pourrait aider les États à avoir accès aux itinéraires commerciaux modernes.Le contrat électronique international constitue une nouvelle sphère qui mérite une recherche analytique afin de lui octroyer une sécurité juridique indispensable à son développement.Ce travail de recherche vise, donc, à élaborer une analyse systématique critique de la réglementation en vigueur qui régit le contrat électronique international et à examiner alors les textes existants aujourd’hui au regard des attentes de l’époque.Il vise à trouver les moyens juridiques susceptibles de garantir plus de sécurité au contrat électronique international.
Keywords: Commerce électronique; Contract; Contrat électronique; Contrat électronique international; Droit commercial (droit international); Electronic contract; International electronic contract; Sécurité juridique

Le droit de l'économie numérique en République Démocratique du Congo à la lumière des expériences européennes et Françaises - Ndukuma Adjayi, Kodjo (Paris 1, 2017)
L'expansion des télécoms et la numérisation sont à la base de la révolution numérique. Leurs aspects sociétaux constituent une véritable source matérielle du droit face au commerce en ligne et à l'économie informationnelle. Le premier axe d'analyse a construit le modèle d'encadrement juridique réalisé à travers le temps pour le commerce en ligne européen et français. La réglementation a suivi l'évolution des techniques de communication à distance : téléachat (1989), contrats à distance (1997), fourniture des services financiers à distance (2002). Mais, la voie électronique a révolutionné les services de la société de l'information, dont la directive 2000/31/CE réglemente les aspects dès 2000. (1) Le deuxième axe appréhende l'évolution des politiques législatives sur les télécoms et les communications électroniques en Europe et en France. Le droit international du commerce a transplanté en Afrique (RDC) les standards juridiques de l'Europe des télécoms, grâce à la mondialisation des marchés, à la diffusion technologique, à l'internationalisation des réseaux et à la multinationalisation. (II) Ainsi, l'ordre juridique congolais a suivi le modèle de dérégulation. L'ouverture des droits de l'accès aux télécoms, jadis monopolistiques, a engagé la transformation des services publics dans l'économie de marché. Partout, le droit de la régulation a suscité des défis nouveaux pour la séparation des fonctions de régulation, d'exploitation et de réglementation. Aussi, la concurrence soulève le défi de l'autorégulation du marché par les forces économiques. (III)Au fil des innovations, la législation telle que pensée au départ en RDC n'est pas en mesure de régir les contingences de la révolution numérique, notamment : les données personnelles et la cybercriminalité. Des travaux de lege ferenda sont en cours depuis avril 2017 au parlement congolais, précisant la prospective de refondation du droit de l'économie numérique en RDC au vu des expériences comparées. (IV). The expansion of telecoms and digitalization has fuelled the digital revolution. Their societal aspects represent a tangible source for legal dealings within the e-commerce and the information economy. The first line of inquiry establishes a model for the legal framework created over time for the European and French e-commerce. It demonstrates that legal adjustments narrowly followed the evolution of telecommunications methods : teleshopping (1989), remote contracts (1997), supplies for remote financial services (2002). However, the rise of this ''electronic gateway'' revolutionized the services of the Information Society, regulated since 2000 by the directive 2000/31/CE. (I)The second line of inquiry analyses the evolution of legislative policies on telecoms and electronic communications in Europe and in France. Because of the globalization of trade, the expansion of technological communications, the internationalization of networks and the growth of multinational firms, the international trade law transferred European legal standards of telecoms in Africa (DRC). (II) Congolese legislation, for instance, has followed the European model of deregulation. By opening rights of access to the telecoms sector, which was previously monopolistic, the country is undergoing the transformation of public services into the market economy. Everywhere, the regulation right creates new challenges for the separation of regulation, operation and control services. In addition, competition raises a new challenge regarding the self-regulation of trade by economic powers. (III) As innovations continue, the initial law of telecoms in RDC is unable to regulate the contingencies of the digital revolution, in particular in the areas of personal data and cybercrime. Since April 2017, the Congolese parliament is working.
Keywords: Commerce électronique; Congo (République démocratique); Cybercrime; Cybercriminalité; Données personnelles; Déréglementation; E-commerce; Economie numérique; Electronic communication; Information economy; Personal data; Protection de l'information (informatique) -- Droit -- Congo (République démocratique); Régulation; République Démocratique du Congo; Telecoms; Télécommunications; Économie numérique

Numérique et grandes notions du droit privé - Netter, Emmanuel (Université de Picardie Jules Verne, 2017)
How to study the rich interactions of law and the digital universe? The most traditional, cross-cutting legal concepts should be placed at the forefront of the analysis. Without denying anything of the specificities of the subject of study, it is important not to give in too quickly to the ease of an entirely new regulation. Connecting digital to common concepts such as the branch to the trunk will allow it to be irrigated with the sap of secular reflections. If, however, the classical instrument is not successfully applied to the new problem, this may be a sign that the venerable concept must be made more flexible, clarified or transformed: it still makes it possible to link digital technology to the achievements of private law, and at the same time can offer the older disciplines the benefit of a better legal instrument. Finally, if and only if the classical notion is absolutely incapable of grasping the difficulty proposed to it, even at the cost of an evolution, the rupture must be established with the common law, and a body of specific rules must be forged.Among the major notions of private law, the person, property and contract are crossed by the digital as if by a groundswell."The person" is divided into two themes: digital identity and electronic communication. The theme of digital identity encompasses issues related to anonymity, its voluntary lifting by online identification techniques, and the collection and use of personal data. The legal and technical tools that allow individuals to shape their digital avatar are subject to detailed critical scrutiny. "Electronic communication" deals both with the adaptation of the rules governing freedom of expression to new forms of specifically digital discourse, the role of technical intermediaries in the fight against hate speech, and the influence of these platforms on the arrangement and filtering of online information."Ownership" is invoked in very different contexts, and coupled with multiple media. Ownership of the infrastructure is first considered. It is being brandished by telecommunication network builders to demand increasing power to deliver information by discriminating according to its content. It arises when we analyze ICANN's global coordination power over domain names, which involves legal and physical control over physical assets. It is then the ownership of the content that is discussed. Applied to works, it makes it possible to observe how copyright accompanies, resists or exploits developments related to digitisation. More unexpectedly, it is proposed to focus on the concept of ownership of "copies of works", which allows consumers of online cultural content to protect the extent of their rights of use against restrictions put in place through technological protection measures. Finally, the ownership of terminals could be invoked by end-users to get out of the ecosystem in which the manufacturer seeks to lock them up, composed of operating systems and specific application stores, which heavily regulate the uses of the devices acquired.The "contract" is undergoing profound changes, which affect both its common rules and its special uses. The common law is changing, first of all, from the point of view of the formation of conventions. Goods and especially online services are placed with maximum speed and efficiency in mind, despite the subtlety of the business models sometimes implemented. The consent given by the clientele is then very poor, and the agreement is fragile in terms of proof and accountability. On the other hand, at the execution stage of agreements, smart contracts are implacable digital sentinels, all the more formidable because they are outside the law. Special contract law is evolving, secondly, in favour of the development of the "collaborative economy", which gives a new lease of life to brokerage, but deeply destabilizes both social and consumer law.
Keywords: Contrats électroniques; Digital platforms; Données personnelles; Freedom of speech; Identité Numérique; Liberté d'expression; Neutralité du net; Personal data; Plateformes numériques; Réseaux sociaux Internet; Smart Contracts; Social network; Uberisation

L'encadrement juridique de "Documents Transférables Électroniques" - Gamal Eldine, Nabil (Université de Montpellier, 2017)
L’intérêt de la présente recherche est d'étudier d’une manière générale les communications électroniques dans le commerce international, et puis à titre particulier d’interpeler les nouveaux défis qui relèveraient de l’utilisation des "documents transférables électroniques", en réfléchissant sur les différentes approches et les méthodes à adopter afin de remédier aux éventuelles déficiences technologiques, identifier puis combler les lacunes juridiques qui se révéler lors de ces échanges. Il s’agirait donc d’une enquête sur les questions juridiques liées à la création, à l’utilisation et à l’exécution du "document transférable électronique" ; il s’agit d’un terme crée par la CNUDCI, ce qui renvoie d’une manière générale à l’équivalent électronique d’un instrument transférable négociable ou d’un document titre. Nous identifions principalement les trois grands axes. Premièrement, la protection des données personnelles. Elle fait l’objet de plusieurs réformes législatives. La plus récente est le Règlement européen 2016/679 du 27 avril 2016 qui vise à promouvoir l’utilisation de l’outil informatique, tout en accordant la protection appropriée aux données à caractère personnel. Deuxièmement, l'exigence d’unicité d’un document transférable (« Garantie de singularité »). La garantie de l’unicité d’un document exige qu’il soit le seul qui existe ou bien, que toute copie soit clairement identifiable comme telle. Les conséquences éventuelles de la reproduction non autorisée de tout document transférable électronique donnant au porteur ou au bénéficiaire le droit de demander la remise de marchandises ou le paiement d’une somme d’argent rendent nécessaire l’élaboration de mécanismes pour garantir l’unicité de ces instruments. Troisièmement, la possession du ‘document transférable électronique’ et la notion de contrôle pour l’identification du porteur. Outre le traitement de la question de l’exigence de la singularité, la recherche d’un mécanisme fonctionnellement applicable et équivalent pour satisfaire à l’exigence de la possession matérielle du document papier constitue un défi majeur. Dans la plupart des modèles juridiques régissant les documents transférables électroniquement, la notion de “contrôle” d’un document électronique est utilisée en tant qu’équivalent fonctionnel de la possession ; cela signifie que la personne qui exerce le contrôle du document transférable électronique est considérée comme le porteur habilité à s’en prévaloir. Ces documents électroniques sont gérés par des prestataires de confiance qualifiés pour garantir leur sécurité. The interest of this research is to study in general, the electronic communications in an international context, and then to focus on the ongoing challenges that occur on the field of ''electronic transferable documents''; for this we shall perceive the methods that have been adopted for the purpose of using such documents, in order to prevent eventual technological deficiencies, identifying and filling the legal gaps revealed throughout our study of these new challenges.Therefore we shall comprehend and defy the legal boundaries, in order to create, use and transfer ''electronic transferable documents''. It is a pre-requisite to clearly identify the subject of this study, which is the term 'electronic transferable record, a concept created by UNCITRAL, which refers generally to ' Electronic equivalent of a transferable record (negotiable or non-negotiable) or a document of a legal right.We shall identify the three following main topics:I. The protection of personal data and privacy has been subject to several legislative reforms. The most recent one is the European Regulation 2016/679 dated April 27th, 2016. This reform aims to promote the use of the IT (Information Technology) tools, while granting the appropriate protection to the personal data. These electronic records are managed by qualified services providers.II. Requirement for uniqueness of the record (''Guarantee of uniqueness'')The guarantee of the uniqueness of the document is to ensure that there is only one possible holder and owner of that document, as in the case of paper document, and that any copy is clearly identifiable as such. As a result of an unauthorized reproduction of any electronic transferable record, any such holder or beneficiary shall have the right to request delivery of goods or the payment of a certain sum of money; thus the need to insure the uniqueness of these electronic records.III. The possession of an electronic transferable record.In addition to the above, the need to identify a functional equivalent approach to satisfy the requirement of possession in the case of electronic transferable document, which is a major challenge.IV. Concept of control and identification of the holderIn most legal models governing electronic transferable records, the definition of ''control'' of an electronic document is used as a functional equivalent to possession. That is, the person who controls the electronic transferable record is deemed to be the holder and the one entitled to use it.
Keywords: Bill of Exchange; Billet à ordre; Commerce électronique; Document transférable électronique; E-Commerce; Electronic signature; Gestion électronique de documents; Lettre de change; Promissory note; Signature électronique; Transferable records

E-commerce et protection des données à caractère personnel : vers un renforcement de la protection des données à caractère personnel des consommateurs dans le cadre des opérations de e-commerce. - Maikuchel, Marine (Université Lille 2 Droit et Santé, 2017)
Keywords: Commerce électronique; E-commerce; Propriété industrielle; Protection de l'information (informatique); Protection des données